THE IMPACT OF INTERNAL GREEN MARKETING ON MANAGERS’ ORGANIZATIONAL IDENTIFICATION AND FINANCIAL PERFORMANCE OF ORGANIZATIONS OF THE AGRIBUSINESS SECTOR IN SERBIA - Milanović, Vesna; Bučalina Matić, Andrea; Jurčić, Ana; Miletić, Vesna (Economics of Agriculture, 2022)
The purpose of the paper was to examine the impact of internal green marketing on managers’ organizational identification and the financial performance of the organizations. The empirical research was carried out by an online survey. The model proposed in this paper was tested on a sample of 53 managers of Serbian organizations in the agribusiness sector. For empirical testing of the proposed hypotheses, partial least squares structural equation modeling was used. The findings revealed that the direct eﬀect of internal green marketing on managers’ organizational identification as well as the direct eﬀect of managers’ organizational identification on financial performance is positive and statistically significant. Managers’ organizational identification fully mediates the relationship between internal green marketing and financial performance. This paper can contribute to better understanding of green internal marketing and its eﬀect on organizations, especially in the agribusiness sector. The results can be useful to managers in the agribusiness sector.